Dendrogeomorphology in Evaluating Erosive Processes in an Urban Conservation Unit - Nicolau, Ricardo de Faria; Faria, Karla Maria Silva de; Momoli, Renata Santos; Chagas, Matheus Peres (Anuário do Instituto de Geociências, 2023)
Water erosion is a worldwide problem that has been depleting soils mainly in tropical regions, due to the greater volume of precipitated water. In this sense, recent prediction methods in tropical regions such as dendrogeomorphology are necessary and important to identify and date the influence and correlation between erosion processes and vegetation. This study aimed to understand and scale the erosive processes, through the annual historical recognition of the rate of soil loss and sedimentation, applying the concepts of dendrogeomorphology in the evaluation of the stem and roots of trees of the species of Anadenanthera macrocarpa and Schefflera morototoni, in a conservation unit in the Brazilian Cerrado. Trees were selected in the following soil level conditions: (i) having root exposure, (ii) no exposure (buried), and (iii) no change in soil level (control). Cross-dating was performed using the COFECHA software program, and the information applied in dating scars and abnormal radial growth periods were observed in exposed roots and associated with the beginning of erosion processes. The results indicated that the occurrence of the erosive processes ascertained by anatomical changes in the exposed roots and a most common erosive rains date from 2006, 2008, 2009, 2010, 2012, 2013, 2016 and 2017. While changes in the trunk growth ring width start from 1992, with similar years between the two species of 2013 and 2017. The highest soil accumulation rates were 18.6 mm/year, vertical losses were 500 mm per year and horizontal losses were 665 mm. Finally, there is a positive correlation between the number of scars and an abrupt increase in the growth rings of the exposed roots with the number of erosive rains.